2018
DOI: 10.3892/ol.2018.9179
|View full text |Cite
|
Sign up to set email alerts
|

A TOP2A‑derived cancer panel drives cancer progression in papillary renal cell carcinoma

Abstract: The aim of the present study was to investigate the function of the DNA topoisomerase IIα ( gene and its associated genes in the progression of papillary renal cell carcinoma (PRCC). Online cancer databases, including cBioportal, Oncomine, OncoLnc and Search Tool for the Retrieval of Interacting Genes/Proteins were used to analyze the gene expression profile, function and regulation network in PRCC. The genes that were significantly co-expressed or mutually exclusively expressed with were identified. The genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…These results suggest that higher TOP2A levels lead to EC progression and represent a higher degree of malignancy in EC. In other studies, TOP2A was upregulated in cancer tissues when compared with that of adjacent non-cancerous tissues in breast cancer (Wang et al, 2012), renal cell carcinoma (Ye et al, 2018), ovarian cancer (Erriquez et al, 2015), prostate cancer (De Resende et al, 2013), nasopharyngeal carcinoma (Lan et al, 2014), and colon cancer (Zhang et al, 2018). Furthermore, TOP2A overexpression is a positive tumor metastasis marker and a poor biomarker for prognosis.…”
Section: Discussionmentioning
confidence: 86%
“…These results suggest that higher TOP2A levels lead to EC progression and represent a higher degree of malignancy in EC. In other studies, TOP2A was upregulated in cancer tissues when compared with that of adjacent non-cancerous tissues in breast cancer (Wang et al, 2012), renal cell carcinoma (Ye et al, 2018), ovarian cancer (Erriquez et al, 2015), prostate cancer (De Resende et al, 2013), nasopharyngeal carcinoma (Lan et al, 2014), and colon cancer (Zhang et al, 2018). Furthermore, TOP2A overexpression is a positive tumor metastasis marker and a poor biomarker for prognosis.…”
Section: Discussionmentioning
confidence: 86%
“…TOP2A (Topoisomerase 2-alpha) is a critical enzyme in DNA replication, transcription and regulating the topologic states of DNA. Studies have confirmed that TOP2A is implicated in various types of tumors, such as gastric cancer (Terashima et al, 2017), colon cancer (Hou et al, 2018), pancreatic cancer (Pei, Yin & Liu, 2018) and papillary renal cell carcinoma (Ye et al, 2018). TOP2A is reported to be a novel prognostic marker in renal cell carcinoma (Lu et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…30,33,34 It is also important for the progression of prognostic marker for papillary RCC. 50 Aurora-A (AURKA) and Aurora-B (AURKB) are kinases that play key roles in the regulation of cell-cycle progression. [51][52][53] In addition to cell cycle regulation, Aurora-A is involved in contributing to epithelial-mesenchymal transition (EMT) and stem-like properties of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is upregulated in ccRCC and associated with progression and prognosis, especially survival among patients undergoing surgery, with a more prominent prognostic value among patients with low‐risk disease 30,33,34 . It is also important for the progression of prognostic marker for papillary RCC 50 …”
Section: Discussionmentioning
confidence: 99%